Rancang Bangun Sistem Informasi Data Kebudayaan Pada Instansi Pemerintahan Menggunakan Framework CodeIgniter - Giandari Maulani; Muhamad Yusup; Amarulloh Amarulloh (UNIVERSITAS RAHARJA, 2022)
This research was made with the aim of building an information system for processing cultural data in government agencies. The case study of this research is at a special government agency for the Tangerang area, to be precise at the Disporabudpar (Department of Youth, Sports, Culture and Tourism) Tangerang Regency. This service has important tasks, namely preparing policies, coordinating, fostering and controlling in the field of Culture. In carrying out their duties, both in programs and in cultural activities, they usually include the activities of compiling, collecting and analyzing data and information. For now, this Tangerang Regency Disporabudpar government agency does not yet have a computerized information system in managing cultural data and there is no use of a database system regarding cultural data, so that the data storage process is still manual and still not effective in terms of security. These data are only stored in ordinary documents, so they are less than optimal and ineffective in the processing of cultural data. In this study, the CodeIgniter Framework is used, which is a powerful PHP framework that is elegantly built to create a full-featured Web application. For the analytical method, this study applies the PIECES (Performance, Information, Economy, Control, Efficiency and Services) method in order to create a more optimal design of information systems in presenting data and information, especially Cultural Data in government agencies.